MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK SISWA MELALUI MODEL PEMBELAJARAN PELANGI MATEMATIKA - Diar Veni Rahayu; Ekasatya Aldila Afriansyah (Institut Pendidikan Indonesia, 2015)
One of the mathematical abilities that need to be owned by junior school students is a problem solving ability. By having the ability of problem solving, the students can be a good problem solver in every field that they do later. In fact, there are many junior high school students who have not achieved a good mathematical problem solving, especially in SPLDV topic. This research aims to improve students' problem-solving ability through the application of Pembelajaran Pelangi Matematika model in SPLDV topic. This type of research is a qualitative research using descriptive analysis method, any giving of the treatment was observed through observation sheets of student activity and observation sheet of teacher activities. To know the result of the given treatment, performed the final test and questionnaire. The results obtained from this study are the application of PPM models are able to bring students into the learning situation more meaningful and enjoyablein the process of classroom learning. The strategy of grouping students homogeneously brings independence and confidence of students to solve problems encountered. The steps used by PPM model make students did not feel depressed and even tend to be enthusiastic during the learning process takes place. Enhancing mathematical problem-solving ability of students at the high category and the students have a positive attitude towards the implementation of PPM model.The conclusion from this study is that the application of PPM models can enhance mathematical problem solving ability of students, especially in the SPLDV topic.